The Oxford handbook of organizational paradox - Smith, Wendy K.; Lewis, Marianne W.; Jarzabkowski, Paula; Langley, Ann (Professor) (Oxford handbooks online., 2017)
Organisations are rife with paradoxes, evident in persistent and interwoven tensions for example between stability and change, flexibility and control, diversity and inclusion, long term and short term, social and financial, learning and performing. This handbook investigates paradoxes across various organisational phenomena and levels of analysis.